2022
DOI: 10.1055/a-1921-2109
|View full text |Cite
|
Sign up to set email alerts
|

Single-use duodenoscopes are an efficient tool for emergency ERCP in real life

Abstract: Background: Biliary emergencies are managed by endoscopic retrograde cholangiopancreatography (ERCP) using duodenoscopes which are reusable devices requiring high-level disinfection to minimize the risk of cross-contamination. Recent reports on newly developed single-use duodenoscopes (SUDs) suggest equivalent performance with reusable duodenoscopes, but the effectiveness of SUDs in emergency ERCP has not been studied yet. Method: We conducted a prospective case series of emergency ERCP procedures using SUDs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…[20] While most of these studies included elective procedures, a recent French study confirmed those outcomes also in the setting of emergent ERCPs performed for several indications. [14] Finally, the present study contributes with data in a homogeneous albeit small population.…”
Section: Accepted Manuscriptsupporting
confidence: 58%
See 4 more Smart Citations
“…[20] While most of these studies included elective procedures, a recent French study confirmed those outcomes also in the setting of emergent ERCPs performed for several indications. [14] Finally, the present study contributes with data in a homogeneous albeit small population.…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…While most studies on SUD use for ERCP have been conducted in elective settings, by experienced operators from tertiaryreferral centers [10,11,12,13], only a recent French study conducted on patients with different indications (acute cholangitis, jaundice, etc.) showed that SUDs also could be considered for emergent situations in real life [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations